Management of the Academic Digitalization Program at MA Negeri 2 Pati - Lutfia Richa Ayu Mustika; Nurkolis; Rosalina Ginting (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aims to describe the management of the academic digitalization program at MA Negeri 2 Pati. The focus of the study includes planning, organizing, actuating, and controlling of academic digitalization as a strategic effort to improve the effectiveness, efficiency, and quality of academic services in the context of digital-based school management. This study employed a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observations, and document analysis. The informants consisted of the principal, vice principal for curriculum, and members of the school digitalization team. Data were analyzed using interactive analysis techniques, including data reduction, data display, and conclusion drawing, supported by triangulation. The findings indicate that the academic digitalization program at MA Negeri 2 Pati has been implemented in a planned and integrated manner. Program planning aligns with the school’s vision, organizing is conducted through a dedicated digitalization team, implementation utilizes integrated digital academic systems, and supervision is carried out through regular evaluation to ensure program sustainability. This study can be applied in the fields of educational management, school leadership, and digital transformation in education. The findings are useful for schools and madrasahs as practical references in managing academic digitalization programs to improve academic services, learning processes, and institutional governance in the digital era. The novelty of this study lies in its comprehensive focus on the management of academic digitalization programs from a school management perspective within a madrasah context. This study extends existing research by emphasizing managerial functions as key determinants of successful academic digitalization at the institutional level.